Improving products' ergonomic value using intelligent decision support system - Kaljun, Jasmin (Strojniški vestnik, 2012)
During the process of defining suitable design solutions, a designer has to consider a wide range of influential factors. Ergonomics certainly belongs to more complex ones. Less experienced designers could encounter several problems during this design stage. Although some literature can be found about ergonomic design of hand tools, a designer still has to have amassed quite a lot of experience and knowledge in the field of ergonomic, in order to choose and carry out appropriate design and redesign actions. Existing computer tools for ergonomic design are not able to assist a designer with higher level advice within design process. An intelligent decision support system has been developed in order to overcome this bottleneck. This paper presents a knowledge base, containing ergonomic design knowledge specific for hand tools design. A pneumatic hammer handle design is used as a case study to show how ergonomic design knowledge built in the system is used to improve the ergonomic value of the product.
Keywords: ergonomija; inteligentna podpora; pnevmatsko kladivo; razvoj ročke; ročna orodja; zajemanje znanja